Upaya Meningkatkan Hasil Belajar Matematika Siswa Pada Materi Aljabar dengan Pendekatan Brain Based Teaching - Nurdalilah Nurdalila (Jurnal MathEducation Nusantara, 2018)
This study aims to: 1) to determine whether the Brain Based Teaching approach can improve students 'mathematics learning outcomes and 2) to find out how much percentage improvement in students' mathematics learning outcomes after applying the Brain Based Teaching approach. This research is an action research conducted in 2 cycles. The subject of this research is the students of class VII-1 MTsN Damuli Pekan which amounts to 40 people. Methods of data collection using tests and observations. Data analysis used is quantitative and qualitative analysis. The results showed that there was an increase in the students' mathematics learning outcomes from cycle I and cycle II. Percentage increase of pratindakan result, cycle I and cycle II result of student's mathematics learning that is 65 % with mean value of mathematics learning result 83,5. Keywords : Brain Based Teaching Approach, Mathematics Learning Outcomes